Electro-optic MMI coupler as wavelength demultiplexer for advanced SDM wireless-WDM optical signal converter - Mefina Yulias Rofianingrum; Yui Otagaki; Hiroshi Murata (Universitas Ahmad Dahlan, 2024)
We report the design, fabrication, and experimental results of an optical wavelength demultiplexer for a new wireless-optical signal converter for Beyond-5G/6G mobile communication system. This optical wavelength demultiplexer is based on a lithium niobate (LiNbO3) multimode interference (MMI) coupler and is intended to be applied in an advanced electro-optics modulator (EOM) with ability in converting the space division multiplexing (SDM) wireless-wavelength division multiplexing (WDM) optical signals. The designed MMI coupler displays a high splitting ratio over -13 dB in both O and L bands. The results from the experiments align well with the simulation. The utilization of the MMI coupler in EOM enables the direct conversion of SDM wireless signals to WDM optical signals, without any additional power supply. The modification of the characteristic of a constructed MMI coupler can be achieved by controlling of the applied voltage of the device.